La semplificazione in Toscana La legge n. 40 del 2009 - SIMONCINI, ANDREA (Strumenti per la didattica e la ricerca, 2011)
The need for reform in Italian Public Administration is a fact that no longer calls for justification: the increasing divergence between expectations and performance in the public sector appears to expand in inverse proportion to the success rate of the attempts at reform that have successively been made since the 1990s. Taking this reflection as its cue, the book offers the results of a study inspired by the Tuscan regional law 40/2009, exploring the results and prospects of the process of administrative and regulatory simplification, at both national and regional level. The chosen key, which is crucially interdisciplinary, for the very first time probes the profound meshing of legal and economic aspects, offering elements not only of analysis but also of practical application.